Advances in robotics for additive/hybrid manufacturing: robot control, speech interface and path planning. Issue 3 (16th April 2018) - Pires, J. Norberto; Azar, Amin S.
Abstract : Purpose: This paper aims to introduce the ideas of practical implications of using industrial robots to implement additive/hybrid manufacturing. The process is discussed and briefly demonstrated. This paper also introduces recent developments on human–machine interface for robotic manufacturing cells, namely the ones used for additive/hybrid manufacturing, as well as interoperability methods between the computer-aided design (CAD) data and material modeling systems. It is presented – using a few solutions developed by the authors – as a set of conceptual guidelines discussed throughout the paper and as a way to demonstrate how they can be applied and their practical implications. Design/methodology/approach: The possibility to program the system from CAD information, which is argued to be crucial, is explored, and the methods necessary for connecting the CAD data to material modeling systems are introduced. This paper also discusses in detail the main requirements (also from a system point-of-view) needed for a full implementation of the presented ideas and methods. A few simulations to better characterize the interactions from heat conduction and physical metallurgy were conducted in an effort to better tune the additive manufacturing process. The results demonstrate how the toolpath planning and deposition strategies can be extracted and studied from a CAD model. Findings: The paper fully demonstrates the possibility to use a robotic setup for additive manufacturing applications and shows the first steps of an innovative system designed with that objective. Originality/value: Using the aimed platform, unsupervised net-shaping of complex components will substitute the cumbersome processes, and it is expected that such a visionary concept brings about a significant reduction in cost, energy consumption, lead time and production waste through the introduction of optimized and interactive processes. This can be considered as a breakthrough in the field of manufacturing and metal processing as the performance is indicated to increase significantly compared to the current instruction-dependent methods.